1990
DOI: 10.1002/1097-4679(199009)46:5<551::aid-jclp2270460502>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and mood disturbance associated with the diagnosis and treatment of testis cancer and other malignancies

Abstract: Eighty‐seven men with testis cancer (TC) and 35 men with other cancers (OC) completed measures of mood (Profile of Mood States) and of personality and psychopathology (Millon Clinical Multiaxial Inventory). Effects of primary disease, phase of diagnosis and treatment, locoregional vs. cytotoxic treatment, age, and marital status on these measures were examined. TC patients appeared more distressed during treatment, particularly during cytotoxic as compared to locoregional treatment, than before or after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Nine good, 8 fair, and 2 poor studies evaluated correlates of anxiety. Associations between anxiety and treatment type were consistently nonsignificant in 5 good, 2 fair, and 1 poor studies. One fair study found anxiety was more prevalent in TC survivors treated with 5 or more chemotherapy cycles, but this may be due to the sample having recurrent or refractory disease, which in itself may be anxiety provoking.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nine good, 8 fair, and 2 poor studies evaluated correlates of anxiety. Associations between anxiety and treatment type were consistently nonsignificant in 5 good, 2 fair, and 1 poor studies. One fair study found anxiety was more prevalent in TC survivors treated with 5 or more chemotherapy cycles, but this may be due to the sample having recurrent or refractory disease, which in itself may be anxiety provoking.…”
Section: Resultsmentioning
confidence: 94%
“…Consistently absent (ie, nonsignificant) associations were found between depression and treatment type (6 good and 6 of 7 fair/poor studies) and time since diagnosis/treatment (4 of 5 good studies), although a single good study found depression decreased slightly in the first year post‐orchidectomy then plateaued …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, subsequent cardiovascular events are higher compared with the general population (12). Psychological disturbances, emotional liabilities, physical and/or cognitive tiredness, and depression are common long-term complaints (13). Long-term close follow-up due to the possibility of recurrence expose such patients to anxiety and uncertainty (13).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological disturbances, emotional liabilities, physical and/or cognitive tiredness, and depression are common long-term complaints (13). Long-term close follow-up due to the possibility of recurrence expose such patients to anxiety and uncertainty (13). Understandably, all these events adversely affect the quality of life, which is deteriorated in >1/3 of patients (14).…”
Section: Introductionmentioning
confidence: 99%